The Distribution and Turnover of Bacterial Communities in the Root Zone of Seven Stipa Species Across an Arid and Semi-arid Steppe - Ma, Xiaodan; Chao, Lumeng; Li, Jingpeng; Ding, Zhiying; Wang, Siyu; Li, Fansheng; Bao, Yuying (Frontiers in Microbiology, 2021)
The bacterial communities of the root-zone soil are capable of regulating vital biogeochemical cycles and the succession of plant growth. Stipa as grassland constructive species is restricted by the difference features of east-west humidity and north-south heat, which shows the population substituting distribution. The distribution, turnover and potential driving factors and ecological significance of the root-zone bacterial community along broad spatial gradients of Stipa taxa transition remain unclear. This paper investigated seven Stipa species root-zone soils based on high-throughput sequencing combined with the measurements of multiple environmental parameters in arid and semi-arid steppe. The communities of soil bacterial in root-zone had considerable turnover and some regular variations about structure along the Stipa taxa transition and they are largely determined by climatic factors, vegetation coverage and pH at a regional scale. Bacterial communities had a clear Stipa population-specificity but they were more strongly affected by the main annual precipitation, which resulted in a biogeographical distribution pattern along precipitation gradient, among which, Actinobacteria, Acidobacteria, Proteobacteria and Chloroflexi were the phyla which were most abundant. During the transformation of Stipa taxa from east to west, the trend of diversity shown by bacterial community in the root-zone decreased firstly, and then increased sharply at S. breviflora, which was followed by continuous decreasing toward northwest afterwards. However, the richness and evenness showed an opposite trend, and α diversity had close association with altitude and pH. There would be specific and different bacterial taxa interactions in different Stipa species, in which S. krylovii had the simplest and most stable interaction network with the strongest resistance to the environment and S. breviflora had most complex and erratic. Moreover, the bacterial community was mainly affected by dispersal limitation at certain period. These results are conductive to the prediction of sustainable ecosystem services and protection of microbial resources in semi-arid grassland ecosystem.